ä½¿ç”¨å¤šåª’ä½“æ•™å¦æé«˜LKIAä¸ä¸“ä¸€å¹´çº§ä¼šè®¡ä¸‰çå¦ç”Ÿå¯¹æ±‰å—ç¬”é¡ºçš„å¦ä¹ èƒ½åŠ› - Ernestin, Scarissa; Thamrin, Lily; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£å¤šåª’ä½“æ•™å¦å¯¹å¦ç”Ÿå¦ä¹ æ±‰å—ç¬”é¡ºçš„æ•ˆæžœï¼Œæ˜¯å¦æœ‰æ•ˆæé«˜ Â Â Â å¦ç”Ÿæ±‰å—ç¬”é¡ºçš„å¦ä¹ èƒ½åŠ›ã€‚ç ”ç©¶å¯¹è±¡æ˜¯LKIA ä¸ä¸“ä¸€å¹´çº§ä¼šè®¡ä¸‰ççš„å¦ç”Ÿï¼Œå…±æœ‰32åÂ Â  å¦ç”Ÿï¼ˆç”·ç”Ÿ15åï¼›å¥³ç”Ÿ17åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯è¯¾å ‚å®žè·µæ•™å¦æ³•å’Œæµ‹éªŒæ³•ã€‚æ ¹æ®æœ¬æ–‡çš„æ•™å¦å®žéªŒä»¥åŠå‰åŽæµ‹éªŒçš„ç»Ÿè®¡ä¸Žåˆ†æžï¼Œç¬”è€…äº†è§£åˆ° Â å¤šåª’ä½“æ•™å¦èƒ½æœ‰æ•ˆåœ°æé«˜å¦ç”ŸæŽŒæ¡æ±‰å—ç¬”é¡ºçš„å¦ä¹ èƒ½åŠ›ã€‚ä»Žè€Œå–å¾—ç›¸å½“å¥½çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šæ±‰å—ç¬”é¡ºï¼›æ±‰å—æ•™å¦ï¼›å¤šåª’ä½“æ•™å¦ Abstract : The purpose of this research is to know the effect of multimedia teaching for the student to learn Chinese characters strokes, to know that if it can increase the students ability in learning Chinese characters strokes. The object of this research are students of the first grade of vocation high school LKIA, accounting class three, with total students were 32students (15 male; 17 famele). The research method are classroom practice teaching and a method of test. Based on analysis of the teaching learning process in the classroom and the result in pre-test and test, the writer gets that result imitating teaching method is effective in improving the ability of students in learning Chinese characters stroke. Thus, the students have got a good improvement during learning process. Keywords: Chinese characters strokes; Chinese characters teaching; multimedia teaching